The throwing shoulder: Part 2. A review of the biomechanics and adaptation to overhead throwing. - Appleby, B. (Journal of Australian Strength and Conditioning, 2012)
Overhead throwing in baseball and water polo athletes takes full advantage of the great mobility of the glenohumeral joint. Additionally, the shoulder undergoes specific structural adaptations in order to increase throwing velocity and decelerate the arm during follow through that can complicate glenohumeral health. Increased external rotation range in common in both sports and can be easily measured by coaches in the field. Muscular imbalance between internal and external rotator cuff has also been identified in both sports. It is very important to monitor this ratio in water polo athletes due to the additional swimming load. Improper throwing technique is also a source of shoulder pain and should be assessed in symptomatic throwers. Despite the differences in mechanics between baseball and water polo throwing, athletes from both sports benefit from careful monitoring of shoulder range and throwing volume to minimise injury. Further, the injury prevention exercises that can be incorporated into strength and conditioning (S&C) programs are similar. It is important for S&C coaches to be aware of the adaptations to throwing and implement strategies to minimise the risk of injury. The purpose of this article is to provide an overview of the throwing technique in baseball and water polo and their specific glenohumeral adaptations. Guidelines for throwing and shoulder assessment will also be outlined.